2007
DOI: 10.1038/sj.ki.5002247
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus-associated nephropathy risk in kidney transplants: the influence of recipient age and donor gender

Abstract: Polyomavirus-associated nephropathy (PVAN) is a frequent cause of kidney transplant failure. We determined the risk factors for biopsy-proven PVAN among 1027 recent kidney transplant recipients by univariate and multivariate analyses. The rate of PVAN was determined over an univariate and multivariate analysis over an average of 30 months of follow-up of patients receiving predominantly living donor grafts with antibody induction and sequential surveillance biopsies to detect subclinical graft disease. Seventy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 37 publications
3
20
2
Order By: Relevance
“…There is evidence that these drugs may contribute to the production of the allograft fibrosis (20,27 (20) particularly in high-risk recipients (28). Overall, the findings of this study highlight the fact that the term IF/TA (or CAN) should not be used as a diagnostic term to explain kidney graft loss (15,29).…”
Section: Identifying Specific Causes Of Kidney Allograft Lossmentioning
confidence: 79%
“…There is evidence that these drugs may contribute to the production of the allograft fibrosis (20,27 (20) particularly in high-risk recipients (28). Overall, the findings of this study highlight the fact that the term IF/TA (or CAN) should not be used as a diagnostic term to explain kidney graft loss (15,29).…”
Section: Identifying Specific Causes Of Kidney Allograft Lossmentioning
confidence: 79%
“…The average adult KT patient population is older with median age close to 50 years and a more pronounced net state of immunosuppression. In fact, older age and TAC trough levels greater than 8 ng/mL have been previously implicated as risk factors for PVAN (25)(26)(27). The retrospective analysis by Cosio et al (28) indicated that low-dose TAC may be a successful strategy to prevent BKV replication and disease in KT patients.…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, in response to a high incidence of PVAN tacrolimus doses were reduced starting in 2002 and this was associated with significant reductions in PVAN, better graft function, and less allograft fibrosis at 1 year (31). Additional declines in PVAN followed avoidance of T cell depleting induction in recipients older than 65, a particularly vulnerable group for this infection (32). An unintended consequence of the reduction in PVAN was a reduction in acute rejection because treatment of PVAN requires reductions in immunosuppression that increases risk of rejection.…”
Section: Discussionmentioning
confidence: 99%